PENGUATAN KESADARAN MULTIKULTURAL MELALUI STRATEGI PENDIDIKAN ISLAM BERBASIS BERPIKIR PROFETIK - Naqiba, Muhammad Izzan; Musa Asy’arie; Mahasri Shobahiya (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Prophetic thinking from the perspectives of Kuntowijoyo and Musa Asy’arie needs to be re-examined to ensure its relevance in strengthening multicultural awareness through Islamic education strategies in the contemporary era. This study employs a qualitative method with a library research approach using descriptive-analytical analysis by examining various scholarly sources related to prophetic thinking and its application in Islamic education. The findings indicate that prophetic thinking which grounded in three core dimensions, namely humanization, liberation, and transcendence, as well as three fundamental principles : integrative, reflective, and transformational can serve as a moral and spiritual paradigm for developing inclusive and multicultural Islamic education. Educational strategies based on prophetic values can be internalized through curriculum design, teacher role modeling, and learning processes oriented toward the common good (maslahah) of the community. The formulation of an integrated framework between prophetic thinking and Islamic education thus represents an applicative strategy for fostering tolerant, just, and civilized multicultural awareness within a global society.